2008
DOI: 10.1007/s10585-008-9224-9
|View full text |Cite
|
Sign up to set email alerts
|

Trefoil factor-3 expression in human colon cancer liver metastasis

Abstract: Deaths from colorectal cancer are often due to liver metastasis. Trefoil factor-3 (TFF3) is expressed by normal intestinal epithelial cells and its expression is maintained throughout the colon adenoma-carcinoma sequence. Our previous work demonstrated a correlation between TFF3 expression and metastatic potential in an animal model of colon cancer. The aim of this study was to determine whether TFF3 is expressed in human colon cancer liver metastasis (CCLM) and whether inhibiting TFF3 expression in colon canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 49 publications
1
25
0
1
Order By: Relevance
“…[15] A study revealed that TFF3 was expressed in 100% colonic cancer liver metastasis and in 91% of primary colon cancers at the mRNA and protein level. [21] These data provide direct evidences that TFF3 contributes to the malignant behavior of colonic cancer cells. Abnormal expression of TFF3 has been reported in various human solid tumors, such as breast, prostate, lung and gastric cancer, and elevated expression of TFF3 in these cancers usually indicate poor outcome.…”
Section: Discussionmentioning
confidence: 60%
“…[15] A study revealed that TFF3 was expressed in 100% colonic cancer liver metastasis and in 91% of primary colon cancers at the mRNA and protein level. [21] These data provide direct evidences that TFF3 contributes to the malignant behavior of colonic cancer cells. Abnormal expression of TFF3 has been reported in various human solid tumors, such as breast, prostate, lung and gastric cancer, and elevated expression of TFF3 in these cancers usually indicate poor outcome.…”
Section: Discussionmentioning
confidence: 60%
“…The EphA1receptor/ephrin ligand system has been implicated in tumor progression in a number of malignancies where they are strongly involved in tumorigenesis including metastatsis, angiogenesis and invasion [11], [18]–[20]. Trefoil factor 3 (TFF3) , located at 21q22.3, belongs to a family of small mucin-associated polypeptides that can regulate cancer progression by increasing tumor metastasis [16], [17], [21], [22]. E74-like factor 5 (ELF5) or epithelium –specific ETS factor 2 (ESE2) , located at 11p15-p13, is a member of the ETS family of transcription factors and has been implicated to play a key role in cell proliferation, differentiation, apoptosis and tumorigenesis [17], [23].…”
Section: Discussionmentioning
confidence: 99%
“…TFF3 is overexpressed in a variety of human malignancies including mammary (12), gastric (13,14), prostate (15), hepatocellular (16), and endometrial (17) carcinomas. It has demonstrated prosurvival, proinvasive, and proangiogenic activities in cells derived from several common human solid tumors (18)(19)(20)(21)(22)(23). Although the role of TFF3 in mammary carcinoma remains undefined, the prognostic or predictive value of TFF3 expression in mammary carcinoma has been indicated by several clinical studies.…”
mentioning
confidence: 99%